Resistance Training–Induced Acute Hypoalgesia in Women With Persistent Pain After Breast Cancer Treatment. Issue 3 (28th March 2023) - Rasmussen, G.H.F.; Madeleine, P.; Arroyo-Morales, M.; Voigt, M.; Kristiansen, M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Fogh Rasmussen, GH, Madeleine, P, Arroyo-Morales, M, Voigt, M, and Kristiansen, M. Resistance training–induced acute hypoalgesia in women with persistent pain after breast cancer treatment. J Strength Cond Res 37(3): e16–e24, 2023—The aim of this study was to determine whether a single bout of resistance training (RT) produces acute exercise-induced hypoalgesia (EIH) in breast cancer survivors (BCS) suffering from persistent pain ≥1.5 years after treatment. Twenty individuals with self-reported pain ≥3 on a 0–10 Numerical Rating Scale after treatment for breast cancer completed 3 experimental sessions, (a) familiarization; (b) 1 repetition maximum (1RM) normalization, and (c) training, consisting of 3 sets of 10 repetitions at 60% of 1 repetition maximum. Pressure pain thresholds (PPTs) were measured before and after training for the dorsal and ventral shoulder regions of the affected side. Movement-evoked pain (MEP) and rating of perceived exertion (RPE) were collected immediately after each set. A p -value less than 0.05 was considered statistically significant. The results demonstrated a significant increase in PPTs of the ventral shoulder region after a single bout of RT ( p ≤ 0.05), indicating a localized analgesic response for this area. By contrast, no change was detected in PPTs on the dorsal shoulder region. No significant differences were found in MEP between sessions despite a significant increase in load and RPE during 1RM assessment ( p ≤ 0.05), indicating that MEP was not affected by increase in absolute and relative intensity. In conclusion, a single bout of submaximal RT reduced PPTs for the ventral shoulder region of BCS with persistent pain after treatment and was well tolerated. Hence, RT may be a useful therapeutic tool for managing persistent pain after breast cancer treatment in clinical practice.